Analysis of Tourism Attraction Potential in Ciliwung Muara Bersama as Ecotourism Destination in Jakarta - Awaloedin, Dipa Teruna; Nugraha, Rizki Nurul; Cecilia, Vita (Westscience Press, 2024)
This study examines the potential of tourist attractions in Ciliwung Muara Bersama as an ecotourism destination in Jakarta. This location provides natural beauty and preserved Betawi cultural elements, which constitute potential for development into an attractive and sustainable ecotourism destination. However, the potential inherent in Muara Ciliwung has not been developed into ecotourism attractions to help preserve the environment and contribute to the well-being of the local community. The research method involves collecting primary and secondary data through observation and interviews. Secondary data is obtained from relevant literature studies. A qualitative descriptive approach is used to analyze the data. The research findings indicate that Ciliwung Muara Bersama has attractive tourism potential, including pristine natural beauty, the flow of the Ciliwung River, and Betawi culture. Development efforts with ecotourism principles are necessary to optimize this potential, which includes increasing active community involvement, environmental conservation, and improving supporting facilities as key factors for the success of ecotourism development. This research emphasizes that the development of Ciliwung Muara Bersama as an ecotourism destination requires a holistic approach that considers environmental, cultural, and economic aspects. By addressing the existing challenges, the potential of this destination can be optimally realized, providing benefits for the environment, local communities, and visiting tourists.